Introducing Transversal Connectivity Index (TCI) as a method to evaluate the effectiveness of the blue-green infrastructure at metropolitan scale - Artan Hysa (Elsevier, 2021)
This study introduces the Transversal Connectivity Index (TCI) as an ecological indicator for classifying the natural landscape patches by their effective transversal connectivity to the water surfaces. The method applies specifically to urban areas at which the quality of blue-green infrastructure (BGI) is of fundamental importance in reducing the climate change consequences. Effective transversal connectivity among the BGI at the metropolitan scale supplies various ecosystem services in support of nature-based solutions for emerging urban challenges. The TCI value is computed (determined) by integrating a variety of existing and novel landscape indicators into an equation. The connectivity indicators belong to two categories: the intra-patch consists of the isoperimetric quotient, and patch ecological indicator, and the inter-patch ones listed as the band level, the shared border ratio, and the transport fragmentation buffer. The method is tested on the metropolitan zone of Berlin, and the results reveal unconventional findings of the effectiveness of BGI in urbanized landscapes. Despite the abundant green surfaces present in Berlin, only 50% of them have direct access to freshwater surfaces, based on Urban Atlas land use land cover data. The proposed indexing method is reproducible for other metropolitan areas, leading to comparative evaluation of effective BGI, having direct implications with emerging agendas of metropolitan management and policy making like the City Biodiversity Index, the concept of Sponge City, and Sustainable Development Goals.